2010
DOI: 10.1080/10803548.2010.11076831
|View full text |Cite
|
Sign up to set email alerts
|

Facilities for Music Education and Their Acoustical Design

Abstract: Good rehearsal facilities for musicians are essential. Directive 2003/10/EC necessitates that musicians are protected from noise exposure. A code of conduct gives the guidelines how this should be done. This study examines room acoustics recommendations provided by the Finnish code of conduct, and discusses whether they are adequate. Small teaching facilities were measured after renovation and compared to earlier measurements. Teachers' opinions were inquired about the facilities before and after. The renovati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…Por causa disso, na caracterização acústica de salas de ensino e prática musical é imprescindível considerar parâmetros relacionados à qualidade tanto da música quanto da palavra falada, já que esta é importante no processo de ensino, de forma que permita o adequado desenvolvimento profissional de um músico. Nesse sentido, os pré-requisitos acústicos essenciais para salas pequenas de música, com volume menor que 500 m 3 , devem ser elevada isolação sonora, tempos de reverberação curtos e uma distribuição homogênea das reflexões sonoras (TEUBER;VÖELKER, 1993;KOSKINEN;TOPPILA;OLKINUORA, 2010;OSMAN, 2010;HATLEVIK, 2012).…”
Section: Parâmetros Acústicos De Salas De Músicaunclassified
“…Por causa disso, na caracterização acústica de salas de ensino e prática musical é imprescindível considerar parâmetros relacionados à qualidade tanto da música quanto da palavra falada, já que esta é importante no processo de ensino, de forma que permita o adequado desenvolvimento profissional de um músico. Nesse sentido, os pré-requisitos acústicos essenciais para salas pequenas de música, com volume menor que 500 m 3 , devem ser elevada isolação sonora, tempos de reverberação curtos e uma distribuição homogênea das reflexões sonoras (TEUBER;VÖELKER, 1993;KOSKINEN;TOPPILA;OLKINUORA, 2010;OSMAN, 2010;HATLEVIK, 2012).…”
Section: Parâmetros Acústicos De Salas De Músicaunclassified
“…Empirical evidence indicates that as acoustic treatment increases, rather than decreases, risk to the musician's well-being increases because the room is perceived as not having sufficient intensity. The lack of perceived volume, then, results in individuals exerting greater biomechanical force with their instruments (Owens, 2003;Koskinen et al, 2010).…”
Section: Influence Of Acoustic Panels On Listening Effortmentioning
confidence: 99%
“…For example, Behar et al (2018) found sound attenuation for acoustical shields was between 5.8 and 10.7 dB for solo performers, but Luo et al (2018) determined that in authentic orchestral settings, the same shields were not effective due to sound diffusion from both sides of the shield. Koskinen et al (2010) found that acoustical damping treatments decreased sound reverberation time but overall did not reduce music teachers’ sound exposure. When it is not feasible to alter the conditions of the music rehearsal/performance environment, or when treatments are inadequate, exposure to high SPLs may be reduced through the use of properly fitted and inserted earplugs (Woolford et al, 1988).…”
mentioning
confidence: 93%